The integration of Chinese and western values as globalised cultural capital among the Malaysian Chinese / Chan Suet Kay - Chan, Suet Kay (2016)
This study compares the socialisation effects of pursuing Chinese-medium and English-medium education in Malaysia, focusing on the Malaysian Chinese. For this study, they are known as the Chinese-educated and English-educated Malaysian Chinese. In terms of identity, these two groups have been said to differ. Using the framework of cultural capital, which has been widely used in educational research, I compare these identity differences, manifested through worldview, consumption tastes, and ambition. These are also known as the three aspects of cultural capital - the institutionalised, the objectified, and the embodied. Basing my research design on other landmark cultural capital studies, such as the BBC-LSE Great British Class Survey (2013), I have designed a questionnaire that encapsulates these identity expressions. However, I have also included a follow-up interview in order to delve deeper into the phenomenological aspect of these consumption-based identity differences, an aspect which has not been mined in full detail in most similar studies. My findings indicate that cultural globalisation is bringing two formerly disparate value systems into the forefront, repackaging some of its attributes as desirable cultural capital (global habitus), and transmitting these values into Malaysian Chinese youth, who embrace it to remain competitively relevant, regardless of education background. This is done through the platform of the mass media. I thus conclude that in an increasingly borderless world, facilitated by transnational media flows, the Chinese-educated and English-educated Malaysian Chinese are experiencing a convergence.